The Impact of the Delay in Inheritance Distribution on Harmony Within the Extended Family in Darul Makmur District, Nagan Raya Regency - Ricki Fadli; Suarni Abdullah; Aulil Amri (AHKAM, 2025)
This study analyzes the impact of delayed inheritance distribution on family harmony in Darul Makmur District, Nagan Raya Regency, and examines this practice from the perspective of Islamic law. The research is motivated by the frequent postponement of inheritance distribution in the community, which often escalates into disputes and intra-family conflict. Using a qualitative method with a juridical-empirical approach, the study draws on in-depth interviews and document analysis of three delayed inheritance cases that occurred in the villages of Suka Ramai, Ladang Baru, and Ujong Tanjong. The findings reveal that postponing inheritance distribution has detrimental consequences for family relations, including broken communication, jealousy, mistrust, and even open conflict among heirs. From an Islamic legal perspective, delaying inheritance distribution without a valid syar'i reason constitutes an act of injustice because it withholds the rights of others and violates the principle of fairness prescribed in the Qur'an and Sunnah. The study concludes that inheritance should be distributed promptly after the deceased's obligations have been fulfilled in order to safeguard justice, preserve family harmony, and promote overall family well-being.